Transformasi Hukum Keluarga Islam di Indonesia: Analisis Kritis atas Penerapan Kompilasi Hukum Islam (KHI) dalam Konteks Maqashid Syariah - Hafidz Miftahuddin, Abdul; Nafi'ah, Siti (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2024)
This study aims to analyze the implementation of the Compilation of Islamic Law (KHI) in the context of divorce, alimony, and children's rights in Indonesia, as well as its relationship to the principles of Maqashid Syariah. The primary focus of this research is to explore how KHI is applied in religious courts and the challenges faced in its implementation. The findings indicate that although KHI provides a clear legal framework for handling divorce cases and post-divorce rights, its implementation is still influenced by inconsistent understanding among judges, differences in socio-cultural norms, and weak law enforcement mechanisms. Economic and social factors also play a significant role in the difficulties of fulfilling alimony and child custody after divorce. From the perspective of Maqashid Syariah, the study reveals that the application of KHI often does not fully consider the principles of protecting life, property, and lineage, which should be the primary goals in every legal decision. This research suggests the need for enhanced training for judges, stronger enforcement mechanisms, and better integration of Islamic law with Indonesian socio-cultural values to ensure the achievement of more substantial justice.